1991
DOI: 10.1002/tox.2530060404
|View full text |Cite
|
Sign up to set email alerts
|

Microtesting appraisal of ATP and cell recovery toxicity end points after acute exposure of Selenastrum capricornutum to selected chemicals

Abstract: Employing microtesting procedures, intracellular ATP and cell recovery (96‐h cell count determinations) were appraised as toxicity end‐point responses after acute (4‐h) exposure of the green alga Selenastrum capricornutum to metals (Cu2+, Co2+, Cd2‐, Cr3+, Cr6+, Ni2+, Hg2+, Zn2+, B3+), sodium azide, and 4 organic compounds (sodium dodecyl sulphate, 2,4‐dichlorophenol, phenol, tebuthiuron). Except for B3‐, both end points were able to measure acute metal phytotoxicity effects at concentrations of 5 mg · L−1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…With the algal bioassay, 14 of the 15 effluents are still toxic after biodegradation testing and only 5 of these exhibit a drop in toxicity. The greater sensitivity of algae toward inorganic chemicals (Chiaudani and Vighi, 1978;Rai et al, 1981;Hickey et al, 1991) presumably accounts for the fact that the phytotoxic response is less influenced by the biodegradation procedure. Organic interactions during microbial degradation of complex effluents can also give rise to toxic by-products (Atlas, 1986) and may have contributed in maintaining algal toxicity elevated as well.…”
Section: Peep Characteristics Of the Pulp And Paper Sectormentioning
confidence: 99%
“…With the algal bioassay, 14 of the 15 effluents are still toxic after biodegradation testing and only 5 of these exhibit a drop in toxicity. The greater sensitivity of algae toward inorganic chemicals (Chiaudani and Vighi, 1978;Rai et al, 1981;Hickey et al, 1991) presumably accounts for the fact that the phytotoxic response is less influenced by the biodegradation procedure. Organic interactions during microbial degradation of complex effluents can also give rise to toxic by-products (Atlas, 1986) and may have contributed in maintaining algal toxicity elevated as well.…”
Section: Peep Characteristics Of the Pulp And Paper Sectormentioning
confidence: 99%
“…A proportion (30%) in the faeces. Hoffman et al (1975) reported that rats from 2 to 18 months old excreted water : methanol (1 : 1) extraction of samples of macrophytes (Hydrilla sp.) showed measurable quantities approximately 85% of a 10 mg и kg Ϫ1 dose in urine within 24 h of ingestion.…”
mentioning
confidence: 99%
“…Ring-labeled tebuthiuron was EPA 1994). McRae (1991) classified compounds on the basis of their potential to leach with the groundwater mixed with a sandy loam (1.3% organic matter) at a level corresponding to 4.5 kg и ha Ϫ1 and allowed to ''age'' ubiquity score (GUS). Tebuthiuron has a GUS of Ͼ2.8, indicating a high potential to leach through agricultural for 30 d. The soil was then added to the top of a 27 cm column of untreated soil and eluted with 40 mL of tap soil.…”
mentioning
confidence: 99%
“…17,1998 C. Andrén et al 99.5 5,263 2,000 5,000 10,000 500 a Cond ϭ conductivity; Cl ϭ chloride; F ϭ fluoride; BOD ϭ biochemical oxygen demand; COD ϭ chemical oxygen demand; GF/A ϭ glass fiber filter; P tot ϭ total phosphorus; N tot ϭ total nitrogen; NO 23 N ϭ nitrite-nitrate nitrogen; NH 4 N ϭ ammonium nitrogen; AOX ϭ adsorbable organic halogens; EOX ϭ extractable organic halogens; EGOM ϭ extractable gas chromatographable organic matter; PBS ϭ potentially bioaccumulating substances; OPOL ϭ nonpolar aliphatic hydrocarbons; AROM ϭ total extractable aromatic compounds; ALIF ϭ total extractable aliphatic compounds; N-inhib ϭ nitrification inhibition; Mic50-15 through Mic20-30 ϭ Microtox test with 50% effective concentration and a 15-min exposure, and so on; Sele ϭ growth inhibition test with Selenastrum capricornutum. Known causes of Microtox toxicity are many metals and many organic compounds [18][19][20]; Selenastrum is also known to be very sensitive to many metals [21]. c The analytical uncertainty expressed as relative standard deviation of quality control samples.…”
Section: Resultsmentioning
confidence: 99%